Transformational Leadership in Education: Impacts and Practices Toward Enhancing School Performance - Ramos, Ruth (Journal of Interdisciplinary Perspectives, 2025)
This study addresses the persistent issue of improving educational leadership to enhance teacher effectiveness and student outcomes in various institutional settings. Despite the growing interest in transformational and distributed leadership styles, empirical data regarding their practical effects in various educational contexts, particularly in the Philippines, remains limited. The findings demonstrate that the adoption of transformational tactics by educational leaders—such as individualized support and a shared vision—enhanced teacher motivation and cultivated a collaborative school culture. This paper conducts a comprehensive literature review of domestic and international studies to analyze the influence of transformational leadership—characterized by vision articulation, inspirational motivation, individualized support, and collaborative culture—on institutional development, teacher motivation, and student achievement. The findings demonstrate that the adoption of transformational tactics by educational leaders—such as individualized support and a shared vision—enhanced teacher motivation and cultivated a collaborative school culture. It also underscores distributed leadership as an ancillary approach that fosters collaborative decision-making and trust. Key effective strategies include cultivating a clear shared vision, enabling ongoing professional development, integrating digital leadership competencies, and encouraging innovation. Despite these advantages, challenges such as governmental constraints, cultural dynamics, and resistance to change remain significant obstacles. The findings support targeted leadership training and contextually appropriate application to improve the competencies of school leaders. The study emphasizes the imperative for politicians and educational institutions to promote hybrid leadership models that amalgamate transformational and distributed approaches tailored to local circumstances, leverage digital resources, and encourage continuous professional growth. Future empirical investigations are advised to validate these strategies across various educational settings, enabling more adaptable and efficient leadership that addresses contemporary challenges and fosters sustained academic success.